INTERNALISASI NILAI-NILAI TAUHID PADA PROSES KONSELING DALAM MEWUJUDKAN MENTAL YANG SEHAT - Ira Suryani (Universitas Islam Negeri Sumatera Utara Medan, 2018)
Humans as servants as well as khalifah on this earth must have been given by Allah SWT many potentials to be able to perform his duties as a servant as well as khalifah. The rapid flow of globalization and the increasingly demands of life that are increasingly materialistic make people fall asleep and almost forget the essence of life. Konsleing is an effort done to help a person in understanding themselves, understanding the environment, accept themselves, accept the environment, objectively, positively, and dynamically of course in accordance with the mission ketauhidan. How to make a human being truly aware of his situation, his life purpose, and how to live the life has been given guidance or guidance that is revealed through the Messenger of Allah. Therefore, how to internalize the values of ketauhidan in the process of konsleing becomes urgent thing done to realize human beings who have a healthy mental. Keywords: Tauhid, Mental health, Counseling